Indikasi Geografis Sebagai Nilai Tambah Produk Kopi Menuju Pasar Domestik Dan Internasional - Borman, Mohammad Ikbal; Citra Dewi, Marini; Kharismawan, Adiguna (JATISWARA, 2023)
Indonesia is a country blessed with abundant natural resources. This fosters a wide variety of biological resources, thus providing a wide range of potential natural wealth in the form of agricultural, plantation, cultivation, handicraft and forestry products characterized by each region’s geographical features. The potential for coffee products to be used as Geographical Indication product is very large because there are many variants of coffee from different regions in Central Sulawesi, each having its own unique characteristics. The problem is that at this time there has been no real step taken by the parties related to the application and registration of Geographical Indications. This research aims to see how the potential of Central Sulawesi coffee products to be registered as Geographical Indications and see how the role of local government in encouraging applications and registration of geographical indications. This paper focuses on two coffee producing areas, namely Sigi Biromaru Regency and Poso Regency. The data used are primary data in the form of field observations and direct interviews and secondary data in the form of literature studies and regulations on geographical indications, then processed and analyzed using qualitative methods. Data is presented in descriptive form and conclusions are drawn using deductive logic. The result of the research is that it is time for the Central Sulawesi Government to start mapping the potential of Geographical Indication products in Central Sulawesi, especially those that have the potential to give birth to Geographical Indications, to create local product competitiveness and regional competitiveness in national and international trade.